Entrevista en Radio Universidad 102.3 FM - Llivi Ruilova, Danny Vicente (2023)
On radio Universidad 102.3 fm, the first interview of Disaster Risk Engineering of the Faculty of Health and Human Sciences of the UEB was carried out, with the participation of Mgtr. María Vallejo, head of the race; and Mgtr. Gray Barragán Aroca, teacher. The objective of the dialogue, with Mgtr. María Vallejo, was to make known what the career offers to future high school graduates in the province and Ecuadorian territory, such as the professional profile, occupational field, modality and duration.